Suppression of small nucleolar RNA host gene 8 (SNHG8) inhibits the progression of colorectal cancer cells - Md Zahirul Islam Khan; Helen Ka Wai Law (Non-coding RNA Research, 2023)
Colorectal cancer (CRC) is one of the most common gastrointestinal malignancies around the world with high mortality. Accumulating evidences demonstrate that long non-coding RNAs (lncRNAs) play critical roles in CRC tumorigenesis by regulating different pathways of carcinogenesis. SNHG8 (small nucleolar RNA host gene 8), a lncRNA, is highly expressed in several cancers and acts as an oncogene that promotes cancer progression. However, the oncogenic role of SNHG8 in CRC carcinogenesis and the underlying molecular mechanisms remain unknown. In this study, we explored the role of SNHG8 in CRC cell lines by performing a series of functional experiments. Similar to the data reported in the Encyclopedia of RNA Interactome, our RT-qPCR results showed that SNHG8 expression was significantly upregulated in CRC cell lines (DLD-1, HT-29, HCT-116, and SW480) compared to the normal colon cell line (CCD-112CoN). We performed dicer-substrate siRNA transfection to knockdown the expression of SNHG8 in HCT-116 and SW480 cell lines which were expressing high levels of SNHG8. SNHG8 knockdown significantly reduced CRC cell growth and proliferation by inducing autophagy and apoptosis pathways through the AKT/AMPK/mTOR axis. We performed wound healing migration assay and demonstrated that SNHG8 knockdown significantly increased migration index in both cell lines, indicating reduced migration abilities of cells. Further investigation showed that SNHG8 knockdown suppresses epithelial to mesenchymal transition and reduces cellular migratory properties of CRC cells. Taken together, our study suggests that SNHG8 acts as an oncogene in CRC through the mTOR-dependent autophagy, apoptosis, and EMT pathways. Our study provides a better understanding the role of SNHG8 in CRC at molecular level and SNHG8 might be used as novel therapeutic target for CRC management.